Instrumental analysis of ferrous sulfate-containing preparations - Andag, Aurea A.
Two methods for the assay of ferrous ion in ferrous sulfate-containing tablets and capsules are described. The first method is based on the spectrophotometric measurement of the chromophore produced by reacting the ferrous ion with alpha, alpha'-dipyridyl (or 2, 2'-bipyridine). For comparison purposes, the absorbance of the said reaction was also measured via the electrophotomer/colorimeter. The second method used o-phenanthroline as the colorimetric reagent. The absorbance was measured using the same instruments.